Designing with succulents - Baldwin, Debra Lee (Timber Press, 2017)
This new, completely revised second edition of her bestselling classic is a design compendium that is as practical as it is inspirational. Designing with Succulents shares design and cultivation basics; hundreds of succulent plant recommendations; and profiles of 50 easy-care, drought-tolerant companion plants. Lavishly illustrated with 400 photographs, you will find everything you need to visualize, create, and nurture a thriving, water-smart succulent garden.